Intangible Heritage in France: Between Museographical Renewal and “Project Territory” - Poulot, Dominique (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2014)
In this article, Dominique Poulot provides a historical overview of the notion of intangible cultural heritage and its relationship to museum studies in France. He brings the study up to the present day to examine the current impact of intangible cultural heritage on the museums. Since 2006, when France signed the UNESCO Convention for the Safeguarding of Intangible Cultural Heritage, intangible cultural heritage has emerged as an issue of current concern. In the museum world, various institutional intermediaries are being used in order to educate curators about intangible heritage, by way of ICOM France, for example. At the same time, the Mission du patrimoine ethnologique (Ethnological Heritage Mission, or MPE) has initiated a collective reflection concerning the new categories and new framework of activities for intangible cultural heritage issues only very recently considered “ethnological” in nature. Hence intangible heritage would seem to be on the agenda of various state administration bodies according to a top-down process characteristic of the centralized tradition of French museum and heritage organizations. The situation has apparently become even more propitious in this regard since a certain number of recent events have served to highlight the fact that the opposition between the notion of ever-changing social space dear to anthropologists and the enclosure of objects conserved at the museum dear to tangible-culture specialists has become a thing of the past.